Continuous Improvement In Improving The Quality Of Education At SMP IT Abu Bakar Yogyakarta - Khusnul Khasanah; Shabrina Nabiatun Salsabila; Abdul Hopid (Insight School Academy, 2024)
Introduction to The Problem: Education is the main foundation for developing human potential and improving living standards. However, implementing high-quality education requires quality components, including good system planning, suitable educational materials, and teacher competence in delivering materials. SMPIT Abu Bakar Yogyakarta, an integrated Islamic school, is committed to being a school of excellence in terms of international character and science. This study aims to analyze the application of continuous improvement to improve the quality of education at SMPIT Abu Bakar Yogyakarta. Purpose: This study explores how SMPIT Abu Bakar Yogyakarta applies the principle of continuous improvement in four dimensions: organizational management, administration and finance, human resources, and learning. The aim is to find out the strategies and methods used by this school in improving the quality of education and how they impact the achievement of educational goals. Design/methods/approach: Qualitative descriptive research methods are used, with observation, interview, and documentation techniques. Data is collected, reduced, presented, and conclusions drawn. Data triangulation techniques were used to verify the validity of the research data. Findings: SMPIT Abu Bakar Yogyakarta has successfully applied the principle of continuous improvement in organizational management, administration and finance, human resources, and learning. The school has implemented an education and financial management system, improved teacher competence, and used an industry-based technology learning model. The results showed that applying TQM in educational organizations made a real contribution to improving the quality of education. Research implications/limitations: The results of this study provide insight into how schools can apply the principle of continuous improvement to enhance the quality of education. However, this research is limited by the scope of study specific to SMP IT Abu Bakar Yogyakarta and may not be universal for all school conditions. Originality/value: This study adds knowledge on how schools can apply the principle of continuous improvement in education, especially in the context of integrated Islamic schools. The results can be used as a reference for other schools looking to improve the quality of their education.